The circular economy in the textile and apparel industry: A systematic literature review. (20th June 2020) - Jia, Fu; Yin, Shiyuan; Chen, Lujie; Chen, Xiaowei
Abstract: Over the past few decades, sustainable supply chain management practices have been developed to incorporate ecological issues into business by decreasing unintentional destructive effects on the environment in the process of manufacturing and purchasing. At the same time, circular economies push the boundaries of environmental sustainability by highlighting the notion of innovative goods, creating a viable relationship between ecosystems and economic growth. Through a systematic literature review, this paper identifies four themes—drivers, barriers, practices, and indicators of sustainable performance when applying a circular economy in the textile and apparel industry. We establish a conceptual model based on these four themes, which illustrates the relationship between them. We highlight challenges in circular economy implementation and provide some suggestions for managers in the textile and apparel industry. We conclude by suggesting several future research directions.